Influence of the degree of damage and confinement materials on the seismic behavior of RC beam-SRC column composite joints. (1st January 2020) - Xu, Chengxiang; Peng, Sheng; Wang, Chenfei; Ma, Zuotao
Highlights: Influence of damage degrees and confinement materials on seismic behavior of joints. FE models of strengthened joints are calibrated with test results. The predicted models of the shear capacity are good agreement with test results. The results provide useful information for the engineering application. Abstract: The seismic behavior of reinforced concrete (RC) beam-steel-reinforced concrete (SRC) column composite joints strengthened with carbon fiber-reinforced polymer (CFRP) sheets and enveloped steel jackets (ESJ) was investigated. Based on the existing regulations, nine specimens were designed and built to simulate pre-damage loading, rehabilitation with CFRP sheets or ESJ, and destruction tests under lateral cyclic loading to determine the performance of the two reinforcement materials (CFRP sheets and ESJ) for different degrees of seismic damage. An analysis of the hysteretic curves, skeleton curves, ductility, energy dissipation, bearing capacity degradation, stiffness degradation, and strain-displacement curves of the specimens indicated that the two strengthening materials exhibited good reinforcement performance. The ESJ improved the bearing capacity and stiffness of the specimens and the CFRP sheets improved the ductility and energy dissipation of the specimens, thereby improving the seismic behavior of the specimens. The severely damaged specimen strengthened with the CFRP sheets or ESJ did not collapse in a simulated strong earthquake and was similar to or even exceeded the seismic performance of the original specimen; this result is important and applicable to engineering practice. The ductility and energy dissipation was lower for the ESJ-strengthened specimen than the CFRP-strengthened specimen. Therefore, the ESJ material is preferable when only one type of material is used for strengthening the specimen. The seismic performance of the RC beam-SRC column frame joints strengthened with the CFRP sheets and ESJ was simulated using the finite element analysis software ABAQUS. There was a good agreement between the simulation results and the experimental results. It was proved that the simulated and experimental results of the ultimate bearing capacity of the joints in the core zones were in good agreement, which meets the design principle of "strong joint, weak member".